Dinamika Perimbangan Kekuatan China dan India di Selat Malaka - Muhaimin, Ramdhan; Martsela, Putri Yasmin (Universitas Al-azhar Indonesia, 2024)
The Malacca Strait is one of the world’s busiest trade lanes. Located in Southeast Asia region, the Malacca Strait becomes a very strategic sea as connecting Asia and Australia, as well as Pacific region. As its geopolitics condition, many powers have competed to keep going their national interest by influencing the region. India and China are two great power that significantly influencing the region, aside from US and Japan. The both power have same economic and political interests of the Malacca Strait. The both power also have grand strategy of foreign affairs and defense policy that are based on economic growth. India has the Look East Policy, while China moves with Soft Power Policy. The presence of these two great powers in Southeast Asia is very pronounced influence the attitudes and perceptions of the ASEAN countries. This paper aims to provide an overview of balance of power between India and China in Malacca Strait using approach of theory of neo-realism.